Disentangling the Regulatory Response of Agrobacterium tumefaciens CHLDO to Glyphosate for Engineering Whole-Cell Phosphonate Biosensors - Masotti, Fiorella (2024)
Phosphonates (PHTs), organic compounds with astable C−P bond, are widely distributed in nature. Glyphosate(GP), a synthetic PHT, is extensively used in agriculture and hasbeen linked to various human health issues and environmentaldamage. Given the prevalence of GP, developing cost-effective, onsitemethods for GP detection is key for assessing pollution andreducing exposure risks. We adopted Agrobacterium tumefaciensCHLDO, a natural GP degrader, as a host and the source ofgenetic parts for constructing PHT biosensors. In this bacterialspecies, the phn gene cluster, encoding the C−P lyase pathway, isregulated by the PhnF transcriptional repressor. We selected thephnG promoter, which displays a dose-dependent response to GP,to build a set of whole-cell biosensors. Through stepwise genetic optimization of the transcriptional cascade, we created a whole-cellbiosensor capable of detecting GP in the 0.25−50 μM range in various samples, including soil and water.